Catálogo web de contenidos multimedia para promocionar servicios profesionales y artesanales del cantón El Empalme año 2015 - García Macías, Jennifer Lisseth (2016)
The development of each country, region, province or locality through its social and economic impact directly contributes to the progress of these, and that depends on the different mechanisms responsible for this area use for this work, so the political organizations such as GAD, provincial governments and the central government have chosen to promote themselves by using digital tools as it is to create web portals aimed at promoting social, business, sports and cultural aspects of each locality. The following initial research was aimed at creating a digital catalog of web access to provide users with a software tool to be promoted and fostered as a society and have the opportunity to publish their services that can offer in the canton free of charge. To make a reality the development of the application, first it was carried out a depth investigation through surveys to a sample of the residents of the Canton, with the results we perceive the need and feasibility the creation of the some one. For this was designed and intuitive and friendly interface with responsive technology, allowing to detail of his/her advertising using multimedia content through via any device including mobiles. Keywords: catalog, media, promotion, responsive, mobiles.